Hepatitis Delta Virus Detected in Salivary Glands of Sjögren's Syndrome Patients and Recapitulates a Sjögren's Syndrome-Like Phenotype in Vivo - Melodie L. Weller; Matthew R. Gardener; Zoe C. Bogus; Michael A. Smith; Elisa Astorri; Drew G. Michael; Donald A. Michael; Changyu Zheng; Peter D. Burbelo; Zhennan Lai; Paul A. Wilson; William Swaim; et al. (Case Western Reserve University, 2016)
Background: Low-level, chronic viral infections have been suspect in the development of select autoimmune diseases, including primary Sjögren's syndrome (pSS). Multiple studies have shown stimulation of antiviral response pathways in pSS tissues suggestive of a viral infection. Yet, with this data in hand, a causal link between a viral infection and development of pSS had not been identified. Therefore, a study was designed to further define the viral landscape within pSS-affected salivary gland tissue to identify potential viral-mediated triggers in the pathogenesis of this autoimmune disease. Methods: A viral microarray was utilized to measure viral transcripts present in salivary gland tissue from patients diagnosed with pSS compared to healthy controls. Murine models of salivary gland localized HDV antigen expression were developed to evaluate the capacity of a chronic HDV signature to trigger the development of a pSS-like phenotype. Results: Through this analysis, two distinct viral profiles were identified, including the increased presence of hepatitis delta virus (HDV) in 50% of pSS patients evaluated. Presence of HDV antigen and sequence were confirmed in minor salivary gland tissue. Patients with elevated HDV levels in salivary gland tissue were negative for detectible hepatitis B virus (HBV) surface antigen and antibodies to HBV or HDV. Expression of HDV antigens in vivo resulted in reduced stimulated saliva flow, increase in focal lymphocytic infiltrates, and development of autoantibodies. Conclusion: Identification of HDV in pSS patients and induction of a complete pSS-like phenotype in vivo provides further support of a viral-mediated etiopathology in the development of pSS.